2022
DOI: 10.1021/acs.jafc.2c03016
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Hemoglobin Adducts of Acrylamide and Glycidamide with Prevalent Metabolic Syndrome in a Nationwide Population-Based Study

Abstract: Environmental and dietary exposures to acrylamide (AA) have been linked with various metabolic-related outcomes, but the results are mixed. However, the association between long-term exposure to AA and the prevalence of metabolic syndrome (MetS) remains unknown. In this study, we aimed to assess the relationship between hemoglobin adducts of AA, biomarkers of internal exposure to AA, and MetS prevalence among a U.S. nationwide population. MetS patients were defined by meeting three or more of the following fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The means of dietary exposure to acrylamide were 1 and 4 μg/kg·bw/d in general populations and high consumers, respectively, concluding that acrylamide has continuously been a human health concern ( 11 ). Acrylamide intake from dietary sources has been identified as a widely concerned risk factor for neurological disorders, obesity, metabolic syndrome, cardiovascular disease (CVD), and depression symptom from epidemiological studies ( 12 16 ). In addition, it has been found that acrylamide has multiple toxicities, including neurotoxicity, reproductive toxicity, developmental toxicity, and carcinogenicity from in vivo and in vitro studies ( 10 ).…”
mentioning
confidence: 99%
“…The means of dietary exposure to acrylamide were 1 and 4 μg/kg·bw/d in general populations and high consumers, respectively, concluding that acrylamide has continuously been a human health concern ( 11 ). Acrylamide intake from dietary sources has been identified as a widely concerned risk factor for neurological disorders, obesity, metabolic syndrome, cardiovascular disease (CVD), and depression symptom from epidemiological studies ( 12 16 ). In addition, it has been found that acrylamide has multiple toxicities, including neurotoxicity, reproductive toxicity, developmental toxicity, and carcinogenicity from in vivo and in vitro studies ( 10 ).…”
mentioning
confidence: 99%
“…Previous epidemiological studies have supported this evidence that greater consumption of food containing a high acrylamide content was related to a higher risk of obesity and atherosclerotic lipid changes. 46,47…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological studies have supported this evidence that greater consumption of food containing a high acrylamide content was related to a higher risk of obesity and atherosclerotic lipid changes. 46,47 The biological mechanisms underlying the observed interactions between fried food consumption and genetic predisposition to abdominal obesity risk remain unclear. Previous studies observed that fried food consumption was correlated with poor physical activity and excessive energy intake.…”
Section: Papermentioning
confidence: 99%
“…Also, several human studies have shown a link between dietary exposure to acrylamide and various metabolic-related outcomes. Wan et al [46] reported the association between acrylamide-hemoglobin adducts, which are considered as biomarkers of acrylamide exposure, and the prevalence of metabolic syndrome among American adults. There is also evidence that exposure to elevated levels of acrylamide during the prenatal period resulted in increased prevalence of overweight in early childhood [47].…”
Section: The Nitrates and Acrylamide And Redox Status O R I G I N A L...mentioning
confidence: 99%